If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7 = 59 + -7x Reorder the terms: -7 + 4x = 59 + -7x Solving -7 + 4x = 59 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -7 + 4x + 7x = 59 + -7x + 7x Combine like terms: 4x + 7x = 11x -7 + 11x = 59 + -7x + 7x Combine like terms: -7x + 7x = 0 -7 + 11x = 59 + 0 -7 + 11x = 59 Add '7' to each side of the equation. -7 + 7 + 11x = 59 + 7 Combine like terms: -7 + 7 = 0 0 + 11x = 59 + 7 11x = 59 + 7 Combine like terms: 59 + 7 = 66 11x = 66 Divide each side by '11'. x = 6 Simplifying x = 6
| x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 | | 8.5x-6.5=6.8x+10.0 | | 6(v+3)-2v=2(2v+1)-11 | | 12x-3(3x-6)=2x+2 | | 25=13+8d | | 240=170+5d | | 10f+5= | | -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 |